Frontispiece: Electroactive Organic Building Blocks for the Chemical Design of Functional Porous Frameworks (MOFs and COFs) in Electronics. Issue 48 (26th August 2020) - Souto, Manuel; Strutyński, Karol; Melle‐Franco, Manuel; Rocha, João
Abstract : Electroactive organic molecules exhibiting electrical conductivity, redox‐activity, optical or magnetic properties have emerged in recent years as promising building blocks for the design of crystalline porous frameworks, such as metal–organic frameworks (MOFs) and covalent organic frameworks (COFs), with numerous functions in electronics. In this Review, the main electroactive organic building blocks used in the past few years for the design and construction of functional porous materials for application in electronics are summarized with special emphasis on their electronic structure and function relationships. For more details see the Review by J. Rocha, M. Souto et al. on page 10912 ff .